Evaluating the climate change robustness of Canadian protected area management plans - Stephanie Barr; Christopher J. Lemieux; Jen Hoesen; Brooklyn Rushton; Pamela Wright (Geography and Sustainability)
Climate change is increasingly affecting all aspects of protected areas management from changes of species ranges to visitor experiences. Due to these impacts, there is a need for managers to take more robust approaches to considering the implications of climate change on the overall application and efficacy of protected areas management direction, including the achievement of the goals and objectives contained within management plans. Through a systematic and comprehensive content analysis approach, this study assesses the current extent to which climate change is considered in Canadian protected area management plans. Specifically, we evaluated 63 terrestrial protected area management plans against a set of climate robustness principles. Our content analysis revealed that climate change is currently not effectively factored into Canadian protected area management plans with an average climate robustness score of 18 %. Climate robustness score was not found to be correlated with protected area size, International Union for the Conservation of Nature (IUCN) management classification, or jurisdictional authority. Certain climate robustness principles received higher scores across the management plans than others. For example, the principles of ‘diverse knowledge sources’ and ‘addresses climate change’ scored relatively highly whereas ‘climate change vulnerability’ and ‘ecosystem integrity’ received the lowest scores. The lack of integration of ecological integrity considerations in management plans was a particularly noteworthy deficiency considering that this guiding principle is the primary legislative objective of many national and sub-national protected areas in Canada. From this assessment, climate change needs to be more effectively and consistently integrated into protected area management plan development and coordinated across associated planning processes. We discuss the ways in which this can be achieved, for example, by integrating scenario planning into organizational management plan development processes.